Soluble PD-L1 and Circulating CD8+PD-1+ and NK Cells Enclose a Prognostic and Predictive Immune Effector Score in Immunotherapy Treated NSCLC patients. (October 2020) - Mazzaschi, G.; Minari, R.; Zecca, A.; Cavazzoni, A.; Ferri, V.; Mori, C.; Squadrilli, A.; Bordi, P.; Buti, S.; Bersanelli, M.; Leonetti, A.; Cosenza, A; et al.
Highlights: Immune checkpoint inhibitors (ICIs) have shifted the therapeutic approach to NSCLC Reproducible biomarkers of ICI benefit represent an unmet and urgent need Circulating descriptors of cancer-host immune interaction were explored here sPD-L1, CD8+PD-1+ and NK cells enclosed a highly prognostic immune effector score Blood-based multiparametric models might non-invasively predict ICI response Abstract: Introduction: Upfront criteria to foresee immune checkpoint inhibitors (ICIs) efficacy are far from being identified. Thus, we integrated blood descriptors of pro-inflammatory/immunosuppressive or effective anti-tumor response to non-invasively define predictive immune profiles in ICI-treated advanced non-small cell lung cancer (NSCLC). Methods: Peripheral blood (PB) was prospectively collected at baseline from 109 consecutive NSCLC patients undergoing ICIs as first or more line treatment. Soluble PD-L1 (sPD-L1) (immunoassay), CD8+PD-1+ and NK (FACS) cells were assessed and interlaced to generate an Immune effector Score (Ieff S). Lung Immune Prognostic Index (LIPI) was computed by LDH levels and derived Neutrophil-to-Lymphocyte Ratio (dNLR). All these parameters were correlated with survival outcome and treatment response. Results: High sPD-L1 and low CD8+PD-1+ and NK number had negative impact on PFS (P < 0.001), OS (P < 0.01) and ICI-response (P < 0.05). Thus, sPD-L1 high, CD8+PD-1+ low and NK low were considered as risk factors encompassing Ieff S, whose prognostic power outperformed that of individual features and slightly exceeded that of LIPI. Accordingly, the absence of these risk factors portrayed a favorable Ieff S characterizing patients with significantly (P < 0.001) prolonged PFS (median NR vs 2.3 months) and OS (median NR vs 4.1) and greater benefit from ICIs (P < 0.01). We then combined each risk parameter composing Ieff S and LIPI (LDH high, dNLR high ), thus defining three distinct prognostic classes. A remarkable impact of Ieff S-LIPI integration was documented on survival outcome (PFS, HR = 4.61; 95%CI = 2.32-9.18; P < 0.001; OS, HR=4.03; 95%CI=1.91-8.67; P < 0.001) and ICI-response (AUC=0.90, 95%CI=0.81-0.97, P < 0.001). Conclusion: Composite risk models based on blood parameters featuring the tumor-host interaction might provide accurate prognostic scores able to predict ICI benefit in NSCLC patients.